Learning English At Workplace From E-Module To Improve English Proficiency Of Employees At Besilam Village - Rizky Vita Losi; Putra, Eka; Rosida, Sisi; Ardilla, Febby (ASIAN PUBLISHER, 2023)
This research purposed to design and develop an E-Module for English at workplace at Administrative Office in Besilam village. This research used Research and Development (R&D) method with the ADDIE model with five stages; Firstly was analyzing problems, potentials, and needs. Secondly was designing to determine Canva application used, the design/theme of the e-module, and the format. Thirdly is developing the design that has been previously made by using Canva application. In addition, at this stage, a validation test was conducted for the validators, namely material experts, linguists, and media experts to determine the feasibility of the E-Module that has been designed and developed. Fourthly is the implementation. In this stage, a practicality test and effectiveness test were administered to the staff and the instructor. Lastly was the evaluation. At this evaluation stage, the improvement of E-Module that has been given input by material experts, linguists, and media experts. Quantitative and qualitative data were used to collect the information. The research findings proved that the average score for eligibility assessment was 91.34%, the average score for practicality assessment was 95.01%, and the average score for effectiveness was 85. In conclusion, the eligibility assessment was classified as